Pengaruh Return On Equity, Total aset Turnover, Current Ratio, dan Economic Value Added Terhadao Harga Saham Pada Saat Kenaikan Harga Bahan Bakar Minyak (Studi Pada Perusahaan Sub Sektor Transportasi yang Terdaftar Di Bursa efek Indonesia): Studi pada Perusahaan Sub Sektor Transportasi yang Terdaftar di Bursa Efek Indonesia - Virgie, Kadek Adriana; Dewi, Putu Eka Dianita Marvilianti (Universitas Pendidikan Ganesha, 2023)
The stock price is the price of a share that occurs on the market exchange at a certain time which is determined by market players and is determined by the demand and supply of the shares involved in the capital market. This research aims to analyze the influence of Return On Equity, Total Asset Turnover, Current Ratio, and Economic Value Added on stock prices when fuel prices increase partially. The Grand Theory used in this research is signaling theory. The type of data used is secondary data in the form of company quarterly financial reports in the transportation sector. Determination of the sample using the purposive sampling method. The sample in this research was 30 companies with a total of 90 data observations. The data analysis technique used in this research is multiple linear regression analysis. Hypothesis testing results using t statistics. The results of the t statistical test show that the Return on Equity variable has a negative and significant effect on stock prices when fuel prices increase. while the variables Total Asset Turnover, Current Ratio, and Economic Value Added have a positive and significant effect on stock prices when fuel prices increase.